Outside the Colony: Jewish Farmers on the Prairies - Lehr, John C. (Canadian Jewish Studies / Études juives canadiennes, 2024)
Jews who immigrated to the Canadian prairies before 1914 mostly gravitated to urban areas. Those who chose to farm usually located in Jewish agricultural colonies where a full Jewish life was possible. A minority voluntarily settled in small farming communities among non-Jews. Jewish merchants in prairie towns also became involved in agriculture both as farmers and as agricultural traders and dealers. Few Jews chose to settle on homesteads where they were isolated from Jewish social and religious life. In the interwar period, attempts to circumvent restrictions placed on Jewish immigration led Jewish philanthropic agencies to place Jewish refugee immigrants on scattered farms, often isolated from Jewish communities. Although economically unsuccessful the strategy achieved its humanitarian objectives.